2015
DOI: 10.1515/jbcpp-2014-0109
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone ameliorates NLRP3-mediated inflammation in the pancreas of albino Wistar rats fed ethanol and high-fat diet

Abstract: TQ exerts the anti-inflammatory activity probably by downregulating the ASC expression to minimize the maturation of proinflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
(40 reference statements)
2
14
0
Order By: Relevance
“…In the current study, thymoquinone treatment significantly suppressed the TNF-α and IL-6 levels in DM rats. Periyanayagam et al (27) observed that thymoquinone ameliorates NLRP3-induced inflammation in albino Wistar rats administered with ethanol and fed a high-fat diet. Rifaioglu et al (28) demonstrated that thymoquinone has an antioxidative and anti-inflammatory effect in an acute pseudomonas prostatitis rat model.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, thymoquinone treatment significantly suppressed the TNF-α and IL-6 levels in DM rats. Periyanayagam et al (27) observed that thymoquinone ameliorates NLRP3-induced inflammation in albino Wistar rats administered with ethanol and fed a high-fat diet. Rifaioglu et al (28) demonstrated that thymoquinone has an antioxidative and anti-inflammatory effect in an acute pseudomonas prostatitis rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upon SARS-CoV-2 entry into the host cell, the disruption of the intracellular environment via ion redistribution results in the activation of NLRP3 inflammasome that increases the secretion of proinflammatory cytokines: IL-1β, IL-18, IL-6 and TNF, further contributing to the imminent cytokine storm and tissue inflammation during respiratory illness [266]. In this context, TQ could have a promising anti-inflammatory role, where it significantly decreases the mRNA expression of the aforementioned proinflammatory cytokines, IL-18, IL-1β and TNF-α, and inhibits IL-6-signaling [16,17,[267][268][269]. In cancer patients, inflammasomes are also overexpressed, leading to an increased inflammatory status [270,271].…”
Section: The Significance Of Thymoquinone In Other Pathological Processes In Covid-cancer Patientsmentioning
confidence: 99%
“…The tail was employed to inject B16F10 cells, and pulmonary tumor lump production was employed as an outcome measure. Thymoquinone dose-dependently attenuated nodules from 15 to 1 in this model [ 183 ].…”
Section: Inhibitors Of Nlrp3 Inflammasome-driven In Vivo Disease Modelsmentioning
confidence: 99%
“…Thymoquinone has been probed for its NLRP3 related actions on pancreatitis [ 183 ]. Upon thymoquinone exposure (100 mg/kg p.o.…”
Section: Inhibitors Of Nlrp3 Inflammasome-driven In Vivo Disease Modelsmentioning
confidence: 99%